2002
DOI: 10.1177/070674370204700710
|View full text |Cite
|
Sign up to set email alerts
|

Risperidone Decreases Craving and Relapses in Individuals with Schizophrenia and Cocaine Dependence

Abstract: P revious research suggests that 16% to 50% of individuals with schizophrenia abuse cocaine (1-3). The prevalence of cocaine abuse in persons with schizophrenia is problematic, considering the debilitating effect that the drug can have on acute symptoms and on illness course. Individuals with schizophrenia and cocaine dependence display more positive symptoms, fewer negative symptoms, and higher rates of extrapyramidal symptoms (EPS) (4,5), which may result from an interaction between dopamine and the psychost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
6

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(47 citation statements)
references
References 26 publications
1
40
0
6
Order By: Relevance
“…Also, in a previous study (6), risperidone decreased positive urinary tests significantly more than zuclopenthixol in subjects with schizophrenia and SUDs. Smelson and others showed that individuals with schizophrenia and cocaine dependence treated with risperidone had significantly fewer cue-elicited cravings and relapses than did subjects treated with typical antipsychotics (7). Indirect evidence of the greater efficacy of risperidone can be found in other studies.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Also, in a previous study (6), risperidone decreased positive urinary tests significantly more than zuclopenthixol in subjects with schizophrenia and SUDs. Smelson and others showed that individuals with schizophrenia and cocaine dependence treated with risperidone had significantly fewer cue-elicited cravings and relapses than did subjects treated with typical antipsychotics (7). Indirect evidence of the greater efficacy of risperidone can be found in other studies.…”
Section: Discussionmentioning
confidence: 98%
“…Despite high comorbidity and the impact of substance use on the outcome of schizophrenia, controlled studies assessing the effectiveness of pharmacologic treatment in this type of patient are rare (5). In 2 recent studies, risperidone decreased relapse for substances more than typical neuroleptics in subjects with schizophrenia and substance abuse (6)(7). However, owing to compliance problems, many psychiatrists tend to prefer using depot neuroleptics to ensure better compliance and to reduce exacerbations and hospitalization in these patients (8,9).…”
mentioning
confidence: 99%
“…Kokain bağımlısı şizofreni tanılı hastalarda risperidon kullanımının relaps ve madde alma isteğinde azalmaya yol açtığını bildiren çalışmalar mevcuttur. [78] Yapı-lan bir çalışma ve iki olgu sunumu sonucuna göre, olanzapin kullanımı şizof-reni tanılı bireylerde kokain kullanma isteğini azaltıyor gibi görünüyorsa da, [79][80][81] başka bir çalışmada diğer atipik ajanlara göre üstünlüğü bulunmamıştır. [82] Parsiyel dopamin agonisti olan aripiprazol kullanan 10 hasta ile yapılan çalışma sonucunda kokain kullanım bozukluğu eş tanısı olan şizofreni tanılı hastalarda kokain kullanımını azalttığı bildirilmiştir.…”
Section: Tedavi Psikoterapiunclassified
“…Bien que la clozapine soit pour l'instant l'antipsychotique atypique le plus souvent associé à une stabilisation de l'état mental, à une diminution des états de besoin 1 de cocaïne et à une réduction de la consommation de substances intoxicantes chez les individus présentant à la fois un trouble sévère et persistant et un trouble lié à une substance, d'autres antipsychotiques atypiques tels que la quétiapine, l'olanzapine ou la rispéri-done se sont également révélés efficaces dans le traitement de cette double problématique et mériteraient, par conséquent, d'être étudiés davantage (Noordsy, O'Keefe, Mueser & Xie, 2001 ;Smelson, Losonczy, Davis, Kaune, Williams & Ziedonis, 2002 ;Brown, Netjek, Perantie & Bobadilla, 2002 ;Green, 2006 ;Stuyt, Sabjel & Allen, 2006).…”
Section: Effets De La Médication Psychotrope Sur Les Troubles Liés à unclassified